Reviews of Books (International review of mission, 1942)
Book reviewed in this article: CHRISTIAN DOCTRINE: CHRISTIAN DOCTRINE. By J. S. WHALE, D.D. A JEW ON CHRISTIANITY: WHAT I BELIEVE. By SHOLEM ASCH. AFRICAN FREEDOM: THE COLOUR BAR IN EAST AFRICA. By NORMAN LEYS. AFRICAN FREEDOM: THE CASE FOR AFRICAN FREEDOM. By JOYCE CARY. AN ANTHROPOLOGIST IN WEST AFRICA.: THE SOCIAL ORGANIZATION OF THE GÃ PEOPLE. BY M. J. FIELD, Ph.D. ‘THE QUESTION OF THE STRAITS’: TURKEY AT THE STRAITS, A BRIEF HISTORY. By JAMES T. SHOTWELL and FRANCIS DEÁK. POLICIES AND ISSUES IN THE PACIFIC: WAR AND DIPLOMACY IN EASTERN ASIA. By CLAUDE A. BUSS. INDIAN ASHRAMS: ASRAMAS, PAST AND PRESENT. By P. CHENCHIAH, V. CHAKKARAI and A. N. SUDARISANAM. THE DISPERSION OF THE TAMIL CHURCH: THE DISPERSION OF THE TAMIL CHURCH. By N. C. SARGANT. THEOLOGICAL EDUCATION IN CHINA: THE DEVELOPMENT OF PROTESTANT THEOLOGICAL EDUCATION IN CHINA, IN THE LIGHT OF THE HISTORY OF THE EDUCATION OF THE CLERGY IN EUROPE AND AMERICA. Part II. By C. STANLEY SMITH. THE COLONIAL BISHOPRICS FUND: THE OVERSEA EPISCOPATE: Centenary History of the Colonial Bishoprics Fund. By W. F. FRANCE. AN AMERICAN OBSERVER IN CHINA: DAWN WATCH IN CHINA. By JOY HOMER.